Penghayatan Siswa Terhadap Pengintegrasian Ilmu Aqli dan Naqli dalam Amalan Kehidupan - Noor Omar, Mohd; Mahdi Yusuf, Sri Andayani (Jurnal Ikhtibar Nusantara, 2022)
This study aims to identify the stages of student appreciation for integrating aqli and naqli knowledge in life practice. This study uses a quantitative approach with a survey method using a probing technique. A total of 731 level Four students were involved in this study. Data were analyzed using the Statistical Package for Social Science (SPSS) version 25.0. The results showed that students at the National High School were able to properly integrate the knowledge of aqli and naqli, especially in the practice of daily life. The findings of the study also illustrate that the integration of aqli and naqli knowledge taught in the size of the Islamic education curriculum gives a good impression on students' lives. The implications of the study show that the integrated approach to the science of aqli and naqli which is included in the teaching and learning process can improve the good character of students to choose appropriate actions in solving situations that apply at the time they are.